Using Songs to Facilitate English Vocabulary Learning Among Indonesian High School Student`s - Sri Ratna Nur Citra Dewi; Abid; Irmawaty Umar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research investigated the effectiveness of using English songs to improve vocabulary mastery among eighth-grade students at MTs Al-Huda Gorontalo. A quantitative approach with a pre-experimental one-group pre-test–post-test design was employed. The participants consisted of 26 students from one eighth-grade class. The treatment was conducted in four sessions using two English religious songs, Thank You Allah and Insya Allah by Maher Zain. The vocabulary instruction focused on three categories: nouns, verbs, and adjectives. Data were analyzed using descriptive statistics and a paired sample t-test. The results showed a substantial improvement in students’ vocabulary mastery after the treatment. The mean score increased from 67.50 in the pre-test to 89.62 in the post-test. The paired sample t-test revealed a statistically significant difference between the two tests (t = –9.802, p < 0.05). These findings indicate that song-based instruction significantly enhanced students’ ability to recognize and understand targeted vocabulary items.